RANCANG BANGUN HORIZONTAL GAS CUTTING MACHINE UNTUK PEMOTONGAN PIPA - Setiawan, Rizal Justian; Hidayat, Hari; Putra, Prabasta Berlian; Laksana, Hadi Krida; Putra, Putu Iswara (Politeknik Harapan Bersama Tegal, 2021)
In the fabrication construction course held at the Fabrication Lab, Mechanical Engineering, Yogyakarta State University, it is necessary to provide workpieces in the form of metal pipe with sizes Ø 4“ to Ø 10